The conquest of the dark spaces: An experimental approach to lighting systems in Paleolithic caves. - Mª Ángeles Medina-Alcaide; Diego Garate; Iñaki Intxaurbe; José L Sanchidrián; Olivia Rivero; Catherine Ferrier; Mª Dolores Mesa; Jaime Pereña; Iñaki Líbano (PLoS ONE, 2021)
Artificial lighting was a crucial physical resource for expanding complex social and economic behavior in Paleolithic groups. Furthermore, the control of fire allowed the development of the first symbolic behavior in deep caves, around 176 ky BP. These activities would increase during the Upper Paleolithic, when lighting residues proliferated at these sites. The physical peculiarities of Paleolithic lighting resources are very poorly understood, although this is a key aspect for the study of human activity within caves and other dark contexts. In this work, we characterize the main Paleolithic lighting systems (e.g., wooden torches, portable fat lamps, and fireplaces) through empirical observations and experimental archeology in an endokarstic context. Furthermore, each lighting system's characteristic combustion residues were identified to achieve a better identification for the archaeological record. The experiments are based on an exhaustive review of archaeological information about this topic. Besides, we apply the estimated luminous data of a Paleolithic cave with Paleolithic art (Atxurra in northern Spain) in 3D through GIS technology to delve into the archeologic implications of illumination in Paleolithic underground activities.